ALTERATION OF BONE MINERAL DENSITY IN BREAST CANCER FEMALE SURVIVORS ON CHEMOTHERAPY TREATMENT: AN INTEGRATIVE REVIEW - Gonçalves, Larissa Vaz; Faria, Sara Socorro; Mota, Jordana Carolina Marques Godinho; Martins, Karine Anusca; Freitas-Junior, Ruffo (Mastology, 2017)
Introduction: Chemotherapy for treatment of patients with breast cancer has increased the survival of this population. However, it can significantly reduce bone mineral density (BMD). Objective: To verify bone mineral density modifications in women with breast cancer undergoing chemotherapy, as well as their clinical characteristics and risk factors. Methods: Integrative review of papers published from 2006 to 2016, carried out through specific terms in PubMed and SciELO databases. Results: In that period, 898 papers were identified (897 in PubMed and 1 in SciELO). Among the six papers recovered, there was a considerable reduction in lumbar spine and femoral bone mass. For women submitted to chemotherapy, the main regimens associated with the reduction were doxorubicin and cyclophosphamide (AC), cyclophosphamide, methotrexate and 5-fluorouracil (CMF) and cyclophosphamide, epirubicin and 5-fluorouracil (FEC). In addition, there was greater BMD reduction among women aged more than 50 years, Caucasian and who presented early ovarian failure induced by chemotherapy. Conclusion: The use of chemotherapy for breast cancer may lead to bone mass loss, especially when AC, CMF and FEC are used in women aged more than 50 years and among those with early menopause due to this treatment.